Radio Immuno Imaging and Therapy - P Raghu Obul Reddy; M C Shashikanth; I M Ali (Wolters Kluwer Medknow Publications, 2006)
Inherent in the application of advances in biomedical science to nuclear medicine is the concept of molecular targeting. Radioimmunoimaging and therapy can add a new dimension to diagnostic imaging and staging of head and neck cancer including metastasis, as well as eradication of disease. The vast majority of malignancies arising in the oral cavity, pharynx, and larynx are squamous cell carcinoma. Radiolabelled MAbs directed against antigens expressed in these neoplasm can be used for tumor detection and selective therapy.